Fine Mapping and Identification of a Novel Phytophthora Root Rot Resistance Locus RpsZS18 on Chromosome 2 in Soybean - Zhong, Chao; Sun, Suli; Yao, Liangliang; Ding, Junjie; Duan, Canxing; Zhu, Zhendong (Frontiers in Plant Science, 2018)
Phytophthora root rot (PRR) caused by Phytophthora sojae is a major soybean disease that causes severe economic losses worldwide. Using soybean cultivars carrying a Rps resistance gene is the most effective strategy for controlling this disease. We previously detected a novel Phytophthora resistance gene, RpsZS18, on chromosome 2 of the soybean cultivar Zaoshu18. The aim of the present study was to identify and finely map RpsZS18. We used 232 F2:3 families generated from a cross between Zaoshu18 (resistant) and Williams (susceptible) as the mapping population. Simple sequence repeat (SSR) markers distributed on chromosome 2 were used to map RpsZS18. First, 12 SSR markers linked with RpsZS18 were identified by linkage analyses, including two newly developed SSR markers, ZCSSR33 and ZCSSR46, that flanked the gene at distances of 0.9 and 0.5 cM, respectively. Second, PCR-based InDel markers were developed based on sequence differences between the two parents and used to further narrow down the mapping region of RpsZS18 to 71.3 kb. Third, haplotype analyses were carried out in the RpsZS18 region using 14 soybean genotypes with whole-genome resequencing. We detected six genes with unique haplotype sequences in Zaoshu18. Finally, quantitative real-time PCR assays of the six genes revealed an EF-hand calcium-binding domain containing protein encoding gene (Glyma.02g245700), a pfkB carbohydrate kinase encoding gene (Glyma.02g245800), and a gene with no functional annotation (Glyma.02g246300), are putative candidate PRR resistance genes. This study provides useful information for breeding P. sojae-resistant soybean cultivars.